SCYPHOSTEGIA BORNEENSIS STAPF*Anatomy of Stem and Leaf in Relation to its Taxonomic Position - C. R. METCALFE (Reinwardtia, 1956)
From an examination of anatomical characters it appears that the genus Scyphostegia is not related to Monimiaceae and Moraceae but represents a separate family related to Flacourtiaceae.